Depression as a Neuroendocrine Disorder: Emerging Neuropsychopharmacological Approaches beyond Monoamines (2019)
Depression is currently recognized as a crucial problem in everyday clinical practice, in light of ever-increasing rates of prevalence, as well as disability, morbidity, and mortality related to this disorder. Currently available antidepressant drugs are notoriously problematic, with suboptimal remission rates and troubling side-effect profiles. Their mechanisms of action focus on the monoamine hypothesis for depression, which centers on the disruption of serotonergic, noradrenergic, and dopaminergic neurotransmission in the brain. Nevertheless, views on the pathophysiology of depression have evolved notably, and the comprehension of depression as a complex neuroendocrine disorder with important systemic implications has sparked interest in a myriad of novel neuropsychopharmacological approaches. Innovative pharmacological targets beyond monoamines include glutamatergic and GABAergic neurotransmission, brain-derived neurotrophic factor, various endocrine axes, as well as several neurosteroids, neuropeptides, opioids, endocannabinoids and endovanilloids. This review summarizes current knowledge on these pharmacological targets and their potential utility in the clinical management of depression.